Temperature and strain rate dependences on hardening and softening behaviours in semi-crystalline polymers: Application to PEEK. (January 2020) - Barba, D.; Arias, A.; Garcia-Gonzalez, D.
Abstract: Semi-crystalline polymers often present a complex non-linear behaviour that combines thermo-viscoelastic and thermo-viscoplastic contributions associated to different deformation mechanisms. During the initial deformation stages, the process is influenced by the rupture and reorientation of crystalline phases while, during the final deformation stages, the process is mainly governed by the mobility and orientation of the amorphous molecular chains. Moreover, the level of reorientation of crystalline and amorphous phases is strongly affected by variables such as temperature and strain rate. This work focusses on the role of such mechanisms in the mechanical behaviour of polyether-ether-ketone (PEEK) within its different thermal-behaviour regions: initial glassy region, glass transition and final rubbery region. To this end, samples of PEEK are subjected to large deformations under uniaxial tension at temperatures from 20 to 240 °C, and strain rates from 0.0001 to 0.1 s − 1 (covering both isothermal and adiabatic conditions). In addition, a constitutive model is proposed to complementarily explain the experimental observations by means of entropic strain hardening due to reorientation of polymer chains influenced by thermo-viscoelastic effects, as well as thermo-viscoplastic behaviours defining the material yielding by means of crystallites deformation and breaking. These results provide new insights into the deformation mechanisms of semi-crystalline polymers below and above glass transition, which are significantly relevant for thermoforming processes of biomedical prosthesis.